Simple combination of oxidants with zero-valent-iron (ZVI) achieved very rapid and highly efficient removal of heavy metals from water. (1st January 2016) - Guo, Xuejun; Yang, Zhe; Dong, Haiyang; Guan, Xiaohong; Ren, Qidong; Lv, Xiaofang; Jin, Xin
Abstract: This study, for the first time, demonstrated a continuously accelerated Fe 0 corrosion driven by common oxidants (i.e., NaClO, KMnO4 or H2 O2 ) and thereby the rapid and efficient removal of heavy metals (HMs) by zero-valent iron (ZVI) under the experimental conditions of jar tests and column running. ZVI simply coupled with NaClO, KMnO4 or H2 O2 (0.5 mM) resulted in almost complete As(V) removal within only 10 min with 1000 μg/L of initial As(V) at initial pH of 7.5(±0.1) and liquid solid ratio of 200:1. Simultaneous removal of 200 μg/L of initial Cd(II) and Hg(II) to 2.4–4.4 μg/L for Cd(II) and to 4.0–5.0 μg/L for Hg(II) were achieved within 30 min. No deterioration of HM removal was observed during the ten recycles of jar tests. The ZVI columns activated by 0.1 mM of oxidants had stably treated 40, 200 (NaClO), 20, 295 (KMnO4 ) and 40, 200 (H2 O2 ) bed volumes (BV) of HM-contaminated drinking water, but with no any indication of As breakthrough (<10 μg/L) even at short empty bed contact time (EBCT) of 8.0 min. The high efficiency of HMs removal from both the jar tests and column running implied a continuous and stable activation (overcoming of iron passivation) of Fe 0 surface by the oxidants. Via the proper increase in oxidant dosing, the ZVI/oxidant combination was applicable to treat highly As(V)-contaminated wastewater. During Fe 0 surface corrosion accelerated by oxidants, a large amount of fresh and reactive iron oxides and oxyhydroxides were continuously generated, which were responsible for the rapid and efficient removal of HMs through multiple mechanisms including adsorption and co-precipitation. A steady state of Fe 0 surface activation and HM removal enabled this simply coupled system to remove HMs with high speed, efficiency and perdurability. Graphical abstract: Highlights: Simple combination of ZVI/oxidants achieves very fast and efficient removal of HMs. ZVI/oxidants can rapidly treat 40, 000 BV polluted water with no As(V) breakthrough. ZVI/oxidants still show high rapidity and efficacy even when As is up to 7500 μg/L. Multiple mechanisms are involved in heavy metal removal by ZVI/oxidants. ZVI/oxidant is cost-effective relative to other HM-adsorptive technologies.